The perception of puerper women from a municipality in the Interior of Tocantins on obstetric violence - Dias , Adriana Moreira; Correia , Italo Schelive; Ribeiro, Gleidy Braga (Seven Editora, 2023)
Laws in Brazil tend to value the dignity of the human person, which, in the health area, reveals the possibility of studying forms of institutional violence suffered by women, and thus drawing a profile of which practices considered violations of rights occur. In practice. The present study aims to identify the perception of women in the municipality of Dianópolis/TO about obstetric violence, based on Law 3.385/2018. The present study is characterized by a qualitative-quantitative nature, in a descriptive way, incurring on the formal inductive method, therefore, techniques/criteria were used to guarantee a better interpretation of the material collected through a questionnaire, previously approved by the Ethics Committee. in Research with Human Beings (CEP) of the State University of Tocantins (UNITINS), by CAAE nº 28 34321-1420.7.0000.8023. The survey was completed in the first half of 2021/1, with a sample population of at least 06 and at most 30 postpartum women. The results obtained showed that women in the municipality perceived, in their deliveries, actions/omissions that are characterized as obstetric violence, in addition. Through the analysis of concepts and narratives, the importance of naming the types of violence suffered by women was inferred; when analyzing the perception of women, it was found that most had no knowledge/perception about the term, but presented events that are Violence Obstetric (VO). Finally, it was discovered the need to broadly discuss public prevention policies, strengthening measures to stop this type of violence. DOI:https://doi.org/10.56238/sevened2023.006-094